2020
DOI: 10.1177/2046147x20920816
|View full text |Cite
|
Sign up to set email alerts
|

#sponsored: Consumer insights on social media influencer marketing

Abstract: Through in-depth interviews with 15 women in the United States, this pilot study contributes to filling the gap in scholarship on consumer perceptions of sponsored content posted by social media influencers (SMI). We found women may follow social media influencers because of prior topic interests, perceived relatability, and authenticity. Social exchange and relationship management theories do not sufficiently account for purchasing decisions despite negative views of consumers. We argue for a new theory calle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
1
33
0
1
Order By: Relevance
“…The results show that this perception is related to emotions of disgust, annoyance, distrust, and support. Furthermore, the consumption motivation of influencer content seems to be associated with prior topic interest, escapism, community, relatability, influencer authenticity, attitudes towards the influencer, subjective norms related to the influencer, influencer-related perceived behavior control, personal relevance, trust, inspiration, and perceived risk (Chopra et al, 2020;Coco and Eckert, 2020).…”
Section: Persuasiveness Of Social Media Influencersmentioning
confidence: 99%
“…The results show that this perception is related to emotions of disgust, annoyance, distrust, and support. Furthermore, the consumption motivation of influencer content seems to be associated with prior topic interest, escapism, community, relatability, influencer authenticity, attitudes towards the influencer, subjective norms related to the influencer, influencer-related perceived behavior control, personal relevance, trust, inspiration, and perceived risk (Chopra et al, 2020;Coco and Eckert, 2020).…”
Section: Persuasiveness Of Social Media Influencersmentioning
confidence: 99%
“…In turn, audiences' relationship is shifted into a humanized reference to the placed product (Jin and Muqaddam, 2019). The absence of the transparency and relatability influences followers to believe the product placement post is "paid"/bought (Coco and Eckert, 2020;Dhanesh and Duthler, 2019) harming parasocial relationships (Lee and Eastin, 2020).…”
Section: Social Media Influencers' (Smis') Product Placementmentioning
confidence: 99%
“…While most researchers agree that ad disclosures increase ad recognition and brand/product recall (Boerman, 2020;, it remains highly contested whether ad disclosures significantly affect brand attitudes or purchase intentions. found that ad disclosures led to negative brand attitudes, yet other studies found that they have no significant impact on brand attitudes or purchase intentions (Coco & Eckert, 2020;Stubb & Colliander, 2019).…”
Section: Ad Disclosurementioning
confidence: 92%